Rural Clinician Scarcity and Job Preferences of Doctors and Nurses in India: A Discrete Choice Experiment - Rao, Krishna D. (Public Library of Science, 2013)
The scarcity of rural doctors has undermined the ability of health systems in low and middle-income countries like India to provide quality services to rural populations. This study examines job preferences of doctors and nurses to inform what works in terms of rural recruitment strategies. Job acceptance of different strategies was compared to identify policy options for increasing the availability of clinical providers in rural areas. In 2010 a Discrete Choice Experiment was conducted in India. The study sample included final year medical and nursing students, and in-service doctors and nurses serving at Primary Health Centers. Eight job attributes were identified and a D-efficient fractional factorial design was used to construct pairs of job choices. Respondent acceptance of job choices was analyzed using multi-level logistic regression. Location mattered; jobs in areas offering urban amenities had a high likelihood of being accepted. Higher salary had small effect on doctor, but large effect on nurse, acceptance of rural jobs. At five times current salary levels, 13% (31%) of medical students (doctors) were willing to accept rural jobs. At half this level, 61% (52%) of nursing students (nurses) accepted a rural job. The strategy of reserving seats for specialist training in exchange for rural service had a large effect on job acceptance among doctors, nurses and nursing students. For doctors and nurses, properly staffed and equipped health facilities, and housing had small effects on job acceptance. Rural upbringing was not associated with rural job acceptance. Incentivizing doctors for rural service is expensive. A broader strategy of substantial salary increases with improved living, working environment, and education incentives is necessary. For both doctors and nurses, the usual strategies of moderate salary increases, good facility infrastructure, and housing will not be effective. Non-physician clinicians like nurse-practitioners offer an affordable alternative for delivering rural health care.